Leonardo's ink bottle the artist's way of seeing - Weir, Roberta (Celestial Arts Publishing, 1998)
"The artist's search for unique, meaningful expression, on paper or canvas, in clay or marble, wood or bronze, is actually mirrored in each of us. Whether we are composing a letter, a song lyric, or a landscape, the desire is the same: to express ourselves easily, elegantly, and eloquently. An artist by vocation and profession, Roberta Weir guides the reader with a steady voice and a sure hand. Part 1 describes the rediscovery of and reliance upon instinct, intuition and inspiration; Part 2 examines the mastery of technique; and Part 3 brings us full circle: having reached a degree of comfort with the nature of inspiration and the mechanics of rendering artistic forms, we are asked to cast it all aside-to stop thinking about it-and just do it."--